No silver bullet - Canonical Poly(ADP-Ribose) Polymerases (PARPs) are no universal factors of abiotic and biotic stress resistance of Arabidopsis thaliana - Rissel, Dagmar; Heym, Peter P.; Thor, Kathrin; Brandt, Wolfgang; Wessjohann, Ludger A.; Peiter, Edgar (Frontiers in Plant Science, 2017)
Abiotic and biotic stress can have a detrimental impact on plant growth and productivity. Hence there is a substantial demand for key factors of stress responses to improve yield stability of crops. Members of the poly(ADP-ribose)polymerase (PARP) protein family, which post-translationally modify (PARylate) nuclear proteins, have been suggested as such universal determinants of plant stress responses. A role under abiotic stress has been inferred from studies in which a genetic or, more commonly, pharmacological inhibition of PARP activity improved the performance of stressed plants. To further elucidate the role of PARP proteins under stress, T-DNA knockout mutants for the three Arabidopsis thaliana PARP genes were subjected to drought, osmotic, salt, and oxidative stress. To exclude a functional redundancy, which was indicated by a transcriptional upregulation of the remaining parp genes, a parp triple mutant was generated. Surprisingly, parp mutant plants did not differ from wild type plants in any of these stress experiments, independent from the number of PARP genes mutated. The parp triple mutant was also analyzed for callose formation in response to the pathogen-associated molecular pattern flg22. Unexpectedly, callose formation was unaltered in the mutant, albeit pharmacological PARP inhibition robustly blocked this immune response, confirming previous reports. Evidently, pharmacological inhibition appears to be more robust than the abolition of all PARP genes, indicating the presence of so-far undescribed proteins with PARP activity. This was supported by the finding that protein PARylation was not absent, but even increased in the parp triple mutant. Candidates for novel PARP-inhibitor targets may be found in the SRO protein family. These proteins harbor a catalytic PARP-like domain and are centrally involved in stress responses. Molecular modeling analyses, employing animal PARPs as templates, indeed indicated a capability of the SRO proteins RCD1 and SRO1 to bind nicotinamide-derived inhibitors. Collectively, the results of our study suggest that the stress-related phenotypes of parp mutants are highly conditional, and they call for a reconsideration of PARP inhibitor studies. In the context of this study, we also propose a unifying nomenclature of PARP genes and mutants, which is currently highly inconsistent and redundant.